A prospective intravascular ultrasound investigation of the necessity for and efficacy of postdilation beyond nominal diameter of 3 current generation DES platforms for the percutaneous treatment of the left main coronary artery. Issue 3 (9th November 2013) - Shand, James A.; Sharma, Divyesh; Hanratty, Colm; McClelland, Anthony; Menown, Ian B.A.; Spence, Mark S.; Richardson, Geoffrey; Herity, Niall A.; Walsh, Simon J.
<x xml:space="preserve">Abstract</x> Objectives To define the size of the left mainstem coronary artery (LMS) in the Northern Irish population and investigate the clinical feasibility, safety, and efficacy of post dilation beyond nominal diameter of current generation Drug eluting stent (DES) when treating the LMS. Background There is no prospective data examining the need, feasibility, and safety of over‐expansion of current generation DES beyond nominal diameter. Methods Patients with flow‐limiting coronary atheroma requiring IVUS assessment of the LMS were recruited. Standardized measurements of the distal LMS were made. Subsequently, patients requiring post dilation of current generation DES within the LMS were entered into a PCI registry. Results Overall, 125 patients were recruited into the initial study. Mean cross‐sectional area (CSA) of the distal LMS was 22.6 mm2 (SD ± 5.4 mm2). Mean maximal vessel diameter was 5.7 mm (SD ± 0.7 mm). Increasing plaque burden was associated with reduced CSA (P < 0.001). In 31 consecutive patients undergoing IVUS guided PCI of the LMS with 5.5 and 6.0 mm balloon catheters, mean maximal stent diameters were >5.0 mm with the Biomatrix Flex 9 crown and Promus Element Large vessel platforms. No intraprocedural complications occurred. Mean follow up was 13.4 months. Clinical restenosis rate was 3.2%, with 2 deaths unrelated to index procedure. Conclusions The majority of patients with angiographic coronary atheroma have a mean LMS diameter of >4 mm indicating the requirement for post dilation beyond nominal diameter all of current generation DES in almost all patients when treating the LMS. This is achievable with current DES platforms with no intraprocedural complication. Clinical follow up indicates excellent short‐term efficacy. © 2013 Wiley Periodicals, Inc.